2003
DOI: 10.2337/diacare.26.10.2835
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3 Months of Continuous Subcutaneous Administration of Glucagon-Like Peptide 1 in Elderly Patients With Type 2 Diabetes

Abstract: OBJECTIVE -Glucagon-like peptide 1 (GLP-1) is an insulinotropic gut hormone that, when given exogenously, may be a useful agent in the treatment of type 2 diabetes. We conducted a 3-month trial to determine the efficacy and safety of GLP-1 in elderly diabetic patients.RESEARCH DESIGN AND METHODS -A total of 16 patients with type 2 diabetes who were being treated with oral hypoglycemic agents were enrolled. Eight patients (aged 75 Ϯ 2 years, BMI 27 Ϯ 1 kg/m 2 ) remained on usual glucose-lowering therapy and eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 39 publications
7
52
0
Order By: Relevance
“…As blood glucose levels are already normalized at 2 weeks after treatment, GLP-1 may not affect fasting glucagon levels at this time. This result is consistent with previous findings, which showed that continuous infusion of GLP-1 or treatment with GLP-1 analog had no effect on fasting glucagon levels (6,43,44). An increase in hepatic triglyceride synthesis and secretion is observed in type 2 diabetes (45).…”
Section: Glp-1 Therapy In Obese Diabetic Micesupporting
confidence: 83%
“…As blood glucose levels are already normalized at 2 weeks after treatment, GLP-1 may not affect fasting glucagon levels at this time. This result is consistent with previous findings, which showed that continuous infusion of GLP-1 or treatment with GLP-1 analog had no effect on fasting glucagon levels (6,43,44). An increase in hepatic triglyceride synthesis and secretion is observed in type 2 diabetes (45).…”
Section: Glp-1 Therapy In Obese Diabetic Micesupporting
confidence: 83%
“…The weight loss as well as reduced gluco-and lipotoxicity induced by GLP-1 were considered likely explanations for the improved insulin sensitivity. Similar findings were made in a study involving 3 mo of continuous subcutaneous infusion of GLP-1 to diabetic subjects (183). However, the same group reported acute augmentation by GLP-1 of insulin-mediated glucose uptake in elderly patients with diabetes (185) and also reported insulin-mimetic effects of GLP-1 in obese subjects compared with nonobese matched controls (60).…”
Section: Whole Body Effects Peripheral Effects and Effects On Insupporting
confidence: 62%
“…In contrast, in a 3-month study in elderly patients switched from oral therapy to continuous GLP-1 infusion, as compared with those remaining on their previous oral therapy, found no effect of GLP-1 on glucagon, and the authors interpreted this as a loss of effect on glucagon with chronic treatment [102]. Another study explored the effects of 1 week of treatment with liraglutide on measures of alpha cell function in patients with type 2 diabetes.…”
Section: Acute Effects Of Exogenous and Endogenous Glp-1 On Alpha Celmentioning
confidence: 99%